THE INFLUENCE OF THE ROLE PLAY METHOD IN TEACHING ENGLISH SPEAKING SKILL TO THE TENTH GRADE STUDENTS AT SMA NEGERI 4 PALEMBANG - Riska Tri Putri; Djunaidi; Etty Pratiwi (Universitas PGRI Palembang, 2025)
This research aimed to assess the impact of the Role-play method in teaching English speaking skill to tenth-grade students at SMA Negeri 4 Palembang. The research method was used a pre-test and post-test one-group design. The population and sample were consist of 292 students from all tenth-grade classes. The researcher selected one class, namely class ten F, consisting of 32 students, After several learning sessions using the role-play method, students were given a post-test to assess the improvement in their speaking skill. The test was used an oral test. The pre-test and post-test assessments were conducted by two raters to ensure the objectivity of the results. The collected data were analyzed using the paired t-test hypothesis testing technique. The inter-rater reliability results for the pre-test were 0.95, indicating that the test was reliable. The inter-rater reliability results for the post-test were 0.99, and the paired t-test calculation result was 24.032. The analysis results showed a significant influence in students speaking skills after the implementation of the Role-play method, as indicated by the significant difference between the pre-test and post-test scores. This research concluded that the role-play method was effective in improving the English speaking skills of tenth-grade students at SMA Negeri 4 Palembang.